Critical Analysis of Data Forwarding Routing Protocols Based on Single path for UWSN - Mukhtiar Ahmed; Mazleena Salleh; Mohammad Ibrahim Channa (International Journal of Electrical and Computer Engineering (IJECE), 2016)
In Underwater Wireless Sensor Network (UWSN); the sensor node is responsible to extract the valuable application based information from underwater environment. The application based information covers the applications like: tactical surveillance, assisted navigation, disaster prevention, offshore exploration, pollution monitoring and oceanographic data collection. The design of routing protocol in underwater environment is one of the challenging issues for researchers. This research article focuses the designing issues of the data forwarding routing protocols based on single path. In this article the designing of 2D and 3D architecture of routing protocols are discussed with their different issues. This article also focuses the analytical approach of proposed routing protocols with different parameters, the simulation scenarios of the single path routing protocols with critical analysis; and the open research issues; will help the researchers to further research in the field of routing protocols for UWSN.